Computed tomography‐guided in vivo cardiac orientation and correlation with ECG in individuals without structural heart disease and in age‐matched obese and older individuals. Issue 4 (2nd April 2015) - Sathananthan, Gnalini; Aggarwal, Gunjan; Zahid, Simmi; Byth, Karen; Chik, William; Friedman, Daniel; Thiagalingam, Aravinda
<x xml:space="preserve">Abstract</x> The cardiac axis in a structurally normal heart is influenced by a number of factors. We investigated the anatomical and electrical cardiac axes in middle‐aged individuals without structural heart disease and compared this with age‐matched obese and older individuals without structural heart disease. A retrospective study of controls included those between 30 and 60 years old with a normal body mass index (BMI), who were then compared with obese individuals between 30 and 60 years old and with individuals more than 60 years old with a normal BMI. The anatomical cardiac axis was determined along the long axis by cardiac computed tomography (CT) and correlated with the electrical cardiac axis on a surface electrocardiogram (ECG) in the frontal plane. A total of 124 patients were included. In the controls (n = 59), the mean CT axis was 38.1° ± 7.8° whilst the mean ECG axis was 51.8° ± 26.6°, Pearson r value 0.12 (P = 0.365). In the obese (n = 36), the mean CT axis was 25.1° ± 6.2° whilst the mean ECG axis was 20.1° ± 23.9°, Pearson r value 0.05 (P = 0.808). In the older group (n = 29), the mean CT axis was 34.4° ± 9.1° whilst the mean ECG axis was 34.4° ± 30.3°, Pearson r value 0.26 (P = 0.209). Obese individuals have a more leftward rotation of both axes than age‐matched normals (P <0.0001), which could be secondary to elevation of the diaphragm. Older individuals have a more leftward rotation only of their electrical cardiac axis (P = 0.01), which could be a normal variant or reflect underlying conduction disturbances in this age group. Clin. Anat. 28:487–493, 2015. © 2015 Wiley Periodicals, Inc.